Protective factors and sources of support in the workplace as experienced by UK foundation and junior doctors: a qualitative study - Anya Göpfert; Maria Van Hove; Carolyn Chew-Graham; Marta Buszewicz; Louis Appleby; James Martin; Farina Kokab; Ruth Riley; Anna K Taylor; Kevin Teoh (BMJ Open)
Objectives This paper reports findings identifying foundation and junior doctors’ experiences of occupational and psychological protective factors in the workplace and sources of effective support.Design Interpretative, inductive, qualitative study involving in-depth interviews with 21 junior doctor participants. The interviews were audio-recorded, transcribed, anonymised and imported into NVivo V.11 to facilitate data management. Data were analysed using a thematic analysis employing the constant comparative method.Setting National Health Service in the UK.Participants Participants were recruited from junior doctors through social media (eg, the British Medical Association (BMA) junior doctors’ Facebook group, Twitter and the mental health research charity websites). A purposive sample of 16 females and 5 males, ethnically diverse, from a range of specialities, across the UK. Junior doctor participants self-identified as having stress, distress, anxiety, depression and suicidal thoughts or having attempted to kill themselves.Results Analysis identified three main themes, with corresponding subthemes relating to protective work factors and facilitators of support: (1) support from work colleagues – help with managing workloads and emotional support; (2) supportive leadership strategies, including feeling valued and accepted, trust and communication, supportive learning environments, challenging stigma and normalising vulnerability; and (3) access to professional support – counselling, cognitive–behavioural therapy and medication through general practitioners, specialist support services for doctors and private therapy.Conclusions Findings show that supportive leadership, effective management practices, peer support and access to appropriate professional support can help mitigate the negative impact of working conditions and cultures experienced by junior doctors. Feeling connected, supported and valued by colleagues and consultants acts as an important buffer against emotional distress despite working under challenging working conditions.